Spiritual coping strategies from the islamic worlview - Normila, Noruddin@Che Ahmad; Rahimah, Embong; Sakinah, Salleh; Zuraidah, Kamaruddin (2015)
This article aims at examining some spiritual or religious coping strategies from the Islamic point of view. It is a matter of fact that religion plays a significant role for an individual in facing complexities and challenges of life. Spiritual or religious coping strategies have been identified as a contributing factor which could affect individual behaviour, and subsequently will affect the communal behaviour. The novel aspect of this article is that apart from drawing theoretical conclusion from the existing work of counseling, is to integrate the Islamic principle pertaining to counseling in a way to address obvious inadequacies in the existing counseling services offered to the Muslims. Therefore, it is appropriate to unearth the influence of religion and religious communities, in this case Islam and Muslims, while they are coping with the challenges and problems. This article provides an overview of related literature covering the wide range of issues pertaining to the Islamic perspective on the problems and coping strategies in general. There are many integrative methods and means that could be derived from the Islamic authentic sources namely the Holy Book (al-Quran), the traditions of the Prophet Muhammad (PBUH) (al-Sunnah) and the Islamic heritage (althurath) as well as the modern methods. From review of the literature, the Islamic coping strategies are categorized into two components. The first is the internal one which consists of acquiring knowledge, spiritual-based experience and faith. The second is the external which comprises social, professional and institutional support. In sum, the collaborative religious coping strategies balance an individual’s own efforts in managing stress by seeking help and support from other people.